2018
DOI: 10.1063/1.5024480
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic frequency tuning of terahertz quantum-cascade lasers

Abstract: We have studied the intrinsic frequency tuning of several terahertz (THz) quantum-cascade lasers (QCLs) based on a hybrid design. With increasing driving current, most QCLs exhibit either a redshift or a blueshift, while some QCLs show both. An oscillator model describes the observed behavior. The accuracy of the model is affected by the complexity of the current-dependent gain spectra of the THz QCLs. Numerical simulations demonstrate a cavity pulling effect insofar as the tuning behavior depends on the reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Since our model is based on approximations for the carrier transport, the simulation results for complex structures are expected to be of limited quantitative accuracy. Similarly, a reduced predictability for complex structures has been observed in the analysis of the currentinduced tuning based on the same model [35].…”
Section: Intersubband Transitionsmentioning
confidence: 61%
See 2 more Smart Citations
“…Since our model is based on approximations for the carrier transport, the simulation results for complex structures are expected to be of limited quantitative accuracy. Similarly, a reduced predictability for complex structures has been observed in the analysis of the currentinduced tuning based on the same model [35].…”
Section: Intersubband Transitionsmentioning
confidence: 61%
“…The onset of the optical gain in a laser leads to a modification of the refractive index and hence to a difference between the frequency of the laser mode and the resonator mode without pumping and lasing. In contrast to the case of most other lasers, frequency pulling in THz QCLs can substantially contribute to the dynamic tuning induced by the injection current [35]. The influence of the gain on the refractive index is further discussed in subsection 3.3.…”
Section: Figure 3(a)mentioning
confidence: 99%
See 1 more Smart Citation
“…While the former process leads to a lowering of the energy of the injector state, it compensates for the latter one, resulting in an extended dynamic range. This allows for a reasonable intrinsic tuning range of the laser modes even for designs with a vertical laser transition as shown recently [16].…”
Section: Designsmentioning
confidence: 87%
“…For the development of more efficient laser schemes for THz QCLs, as well as a low loss waveguide design, the information is needed on the loss in THz QCLs over a wide range of temperatures and frequencies. It is shown that the loss in THz QCLs plays an important role in the internal tuning of the radiation frequency [3]. In this work, we propose to use a double metal waveguide based on silver (Ag), for reducing the losses of the waveguide.…”
mentioning
confidence: 99%